Prevalence of Head Lice (Pediculus humanus capitis) among Primary School Children in Baghdad Suburbs (Medico Legal Update, 2021)
A cross-sectional school-based study was performed with the objectives to determine the prevalence of headlice infestation among primary schools in Baghdad suburbs (Abu Ghraib, Al-Yousifiya, Al-Radwaniyah,Al-Al-Taji, and Al-Hussainiya). The study included examination of 920 male and female students in severalelementary schools’ class first to sixth (age 6-15 year). These schools include urban, rural, and economicallyand culturally diverse regions for the period from February to June 2018. The results of the current studyshowed that the total injury rate was 9%, and the Radwaniyah region recorded the highest infection rate of13.2 and the Al-Al-Taji rejoin region recorded the lowest (6.1%). The female infection rate was greater thanthat of males and reached 12.3 and 5.6 respectively. The results indicated a significant relationship betweenthe spread of head lice and the educational status of parents, sharing of the head comb, and infection withdandruff.